Global lignin supply overview and kraft lignin potential as an alternative for petroleum-based polymers. (May 2020) - Dessbesell, Luana; Paleologou, Michael; Leitch, Mathew; Pulkki, Reino; Xu, Chunbao (Charles)
Abstract: Lignin is an abundant renewable feedstock for bioenergy, chemicals and materials production. Numerous review papers have addressed lignin research; though, a limited focus has been given to lignin commercial initiatives and its market applications potential. However, this is an area of great importance, given the growth of commercial lignin production. For instance, expressed in the strategic directions taken by pulp mills with kraft lignin valorization as a primary pathway in their transformation to the biorefinery. This work aims to provide concrete information on the global lignin market and supply, and to discuss its most explored applications - these being phenols and polyols due to their importance in short- and mid-terms lignin market development. Over the years, lignosulfonates have dominated the market. However, kraft lignin production increased by 150% from 2014 to 2018, competing with lignosulfonates to some extent. Even with the increased kraft lignin precipitation, it should remain a bioenergy source for kraft mills in the short- and mid-terms, with only its surplus being directed to biochemicals and biomaterials. The most demonstrated market application of kraft lignin is the production of biophenol, with biopolyol as a prone application in the mid-term. In both cases, lignin modification to obtain uniform and reactive biochemicals could allow faster market penetration. Besides, phenol and polyol markets are expected to grow globally providing an opportunity for biopolymers. The main recommendations are related to scaling up technologies to achieve technical and economic optimization of lignin applications as well as collaborative research efforts connecting stakeholders in the value chain. Highlights: Kraft lignin recovery in pulp mills worldwide was 265, 000 t in 2018. Lignin modification is vital for superior substitution, enhancement and stability. De-polymerization at mild conditions is a feasible option for lignin upgrading. Promising lignin value-added applications in the short-term are phenols and polyols. In the long-term are thermoplastics and carbon with an expected fast-growing demand.